Merkel cells are integral constituents of desmoplastic trichoepithelioma: an immunohistochemical and electron microscopic study - Hartschuh, Wolfgang; Schulz, Tilman (Journal of cutaneous pathology, 1995)
The incidence of Merkel cells has previously been investigated in a number of inflammatory and tumorous lesions of the skin. Special attention was given to tumors with follicular differentiation. In the present study we examined the localization of Merkel cells in another adnexal tumor, the desmoplastic trichoepithelioma (n= 15), as well as in its main differential diagnosis, the morpheiform basal-cell carcinoma (n=30). Using immunohistochemical methods, we found Merkel cells as a stable constituent in desmoplastic trichoepitheliomas, but failed to detect them in morpheiform basal-cell carcinomas. These findings might therefore be an important tool in the sometimes very difficult but clinically imperative distinction between these two conditions. Furthermore, our study may be of interest in the discussion about the origin of desmoplastic trichoepitheliomas. High numbers of Merkel cells in desmoplastic trichoepitheliomas indicate a bulge-derived origin of this adnexal tumor, since high numbers of Merkel cells, especially in the bulge, were recently discovered. Although the significance of Merkel cell hyperplasia in desmoplastic trichoepithelioma is not presently understood, a regulatory role of the Merkel cell in growth and development of this adnexal tumor is suggested.
Elektronische Reproduktion der Druck-Ausgabe 27. April 2006
Gesehen am 06.08.2025